Light Reflection and Transmission in Structured Composite Material - A.A. Goloborodko (Журнал нано- та електронної фізики)
The paper deals with the optical properties of composite material which consist of dielectric plate with a 2D array of silver nanoparticles. The possibility of describing the reflection and transmission of coherent electromagnetic radiation in a dielectric slab with an array of metal rods by effective medium model was analyzed. The coefficients of reflection and transmission depending on rods filling factor for such medium were calculated. The results of calculations by nonlocal homogenization model were compared with the data of the exact T-matrix method calculations.